PERFORMANSI REFRIGERATOR MODEL MOHAMMAD BAH ABBA - , M SHOLCHAN ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Clay Refrigerator is a clay-based instrument (pottery) which serves to keep food especially vegetables and fruits. It works using the concept of natural evaporation. In this study the inner pot of Clay Refrigerator Mohammed Bah Abba Model replaced with aluminum, while the outer pot still use the pottery. The objective of this study to measure the ability of Clay Refrigerator Mohammed Bah Abba Model in store vegetables and fruits. Testing is done by storing vegetables and fruits into Clay Refrigerator with two different sizes, small and big, then in Clay Refrigerator temperature is measured and compared with the room temperature. Open and close every hour treatment is also carried out on the next stage of testing. Clay Refrigerator was tested in a room with a temperature between 25 Â° C - 31 Â° C. The performance results of Clay Refrigerator small size with loads of vegetables is 110.5 Joule with ÎT average of 5.0 Â° C. While performance for Clay Refrigerator big size is 276.3 ÎT Joule with an average of 5.5 Â° C. The performance results of Clay Refrigerator small size with loads of fruits is 130.4 ÎT Joule with an average of 5.9 Â° C. While performance for Clay Refrigerator big size is 336.6 Joule with an average ÎT 6.7 Â° C.